2019
DOI: 10.1085/jgp.201812243
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic heat pulses activate cardiac thin filaments

Abstract: Muscle fiber contraction involves chemical reactions and structural changes that are sensitive to temperature. Ishii et al. show that rapid heating causes cardiac thin filament sliding, and the data could indicate that thin filaments are partially activated during diastole at mammalian body temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 58 publications
1
36
1
Order By: Relevance
“…Brunet et al (2012) analyzed sliding movements of thin filaments that had been reconstituted with human cTn and Tm at temperatures above ∼43 • C under relaxing conditions in the absence of Ca 2+ (+EGTA). We performed a rapid-heating experiment using infrared laser irradiation and found that thin filaments that had been reconstituted with bovine cTn and human Tm exhibited sliding movements at >∼35 • C in the absence of Ca 2+ (Ishii et al, 2019). Because the sliding velocity was ∼30% at 37 • C compared to the maximum, this previous finding suggests that thin filaments are partially activated in diastole at physiological body temperature, enabling rapid and efficient myocardial dynamics in systole (see Ishii et al, 2019 for details).…”
Section: Thermal Activation Of Thin Filamentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brunet et al (2012) analyzed sliding movements of thin filaments that had been reconstituted with human cTn and Tm at temperatures above ∼43 • C under relaxing conditions in the absence of Ca 2+ (+EGTA). We performed a rapid-heating experiment using infrared laser irradiation and found that thin filaments that had been reconstituted with bovine cTn and human Tm exhibited sliding movements at >∼35 • C in the absence of Ca 2+ (Ishii et al, 2019). Because the sliding velocity was ∼30% at 37 • C compared to the maximum, this previous finding suggests that thin filaments are partially activated in diastole at physiological body temperature, enabling rapid and efficient myocardial dynamics in systole (see Ishii et al, 2019 for details).…”
Section: Thermal Activation Of Thin Filamentsmentioning
confidence: 99%
“…The molecular mechanisms of thermal activation of thin filaments are yet to be fully understood. One possible mechanism is "partial dissociation" of Tn-Tm from F-actin upon increasing temperature (as discussed in Oyama et al, 2012;Ishii et al, 2019); viz., Tanaka and Oosawa (1971) demonstrated that Tm dissociates from F-actin at >∼40 • C. Later experiments by Ishiwata (1978) on reconstituted thin filaments (F-actin plus Tn-Tm) showed that Tn-Tm starts to partially dissociate from F-actin at ∼41 • C, with dissociation temperatures of 48.8 and 47.0 • C in the absence and presence of Ca 2+ , respectively.…”
Section: Thermal Activation Of Thin Filamentsmentioning
confidence: 99%
“…In that study, the [Ca 2+ ] as measured by a calcium indicator (Fluo-4) was the same at 41 °C as in relaxed cells at 36 °C, suggesting that the contraction system of cardiomyocytes is activated at high temperatures even under conditions of very low [Ca 2+ ] 19 . This activation has also been confirmed in an in vitro motility assay using thin filaments reconstituted with α-tropomyosin and troponin 20 . These filaments were found to be able to slide at a rate of approximately 30% of full activity at a temperature of approximately 37 °C even at a low [Ca 2+ ] 20 .…”
mentioning
confidence: 54%
“…This activation has also been confirmed in an in vitro motility assay using thin filaments reconstituted with α-tropomyosin and troponin 20 . These filaments were found to be able to slide at a rate of approximately 30% of full activity at a temperature of approximately 37 °C even at a low [Ca 2+ ] 20 . Adult cardiomyocytes do not show SPOC with temperature jumps, but neonatal cardiomyocytes exhibit oscillatory contraction at high frequencies (6)(7)(8)(9)(10)(11)(12) under conditions of low-frequency Ca 2+ oscillation (~ 1.4 Hz) 18 .…”
mentioning
confidence: 54%
See 1 more Smart Citation